Functional characterization of human brown adipose tissue metabolism. Issue 7 (9th April 2020) - Richard, Marie Anne; Pallubinsky, Hannah; Blondin, Denis P.
Abstract : Brown adipose tissue (BAT) has long been described according to its histological features as a multilocular, lipid-containing tissue, light brown in color, that is also responsive to the cold and found especially in hibernating mammals and human infants. Its presence in both hibernators and human infants, combined with its function as a heat-generating organ, raised many questions about its role in humans. Early characterizations of the tissue in humans focused on its progressive atrophy with age and its apparent importance for cold-exposed workers. However, the use of positron emission tomography (PET) with the glucose tracer [18F]fluorodeoxyglucose ([18F]FDG) made it possible to begin characterizing the possible function of BAT in adult humans, and whether it could play a role in the prevention or treatment of obesity and type 2 diabetes (T2D). This review focuses on the in vivo functional characterization of human BAT, the methodological approaches applied to examine these features and addresses critical gaps that remain in moving the field forward. Specifically, we describe the anatomical and biomolecular features of human BAT, the modalities and applications of non-invasive tools such as PET and magnetic resonance imaging coupled with spectroscopy (MRI/MRS) to study BAT morphology and function in vivo, and finally describe the functional characteristics of human BAT that have only been possible through the development and application of such tools.